Świecka tożsamość polskich Żydów jako żydowska tożsamość alternatywna - Włodarczyk, Tamara (Studia Europaea Gnesnensia, 2013)
The article discusses the issue of Jewish secular identity. Drawing on the studies of Irena Hurwic-Nowakowska, Konstanty Gebert and Heleny Datner, as well as own research, the author demonstrates the specific identity of a number of Polish Jews, whose notion of Jewish identity is not founded on religion but rooted in the broadly understood Jewish heritage.